PENERAPAN ASAS TERANG DAN TUNAI DALAM JUAL BELI TANAH YANG MERUPAKAN HARTA BERSAMA DALAM PERKAWINAN (STUDI PUTUSAN NOMOR 1/PDT.G/2019/PN.LBT) - Desvia Winandra; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2020)
The sale and purchase of land principles in National Land Law is a transfer of land rights that are clear and cash. This means that the transfer of land rights carries out in front of an authorized public official and the payment is being done by cash and simultaneously. The problem of this research ishow to apply the principle of clear and cash in the sale and purchase of land which is a joint property in marriage in the Decision of the Lembata District Court Number 1/Pdt.G/2019/PN.Lbt. The research method used is normative legal research by examining literature through the statute approach and case approach. The result showed the sale and purchase of land in this case was not carried out clearly, because the implementation of the sale and purchase of land was unknown andnot approved by his wife even though the property’s certificate is written in the name of the husband, where the land is joint property. The sale and purchase of land is also not carried out by PPAT, even though the land has a Freehold Certificate which was made by Notary Public/ PPAT of Lembata Regency. Regarding the implementation of the cash principle, the act of buying and selling land are carried out by cash principle even though the payment is made three times, because cashis an agreement about the price, not the payment methods. The principle of clear and cash are important to be remembered in the act of buying and selling land.